2017
DOI: 10.1021/acssensors.7b00104
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Detection of Small Organic Molecules by Molecularly Imprinted Polymer Functionalized Thermocouples: Toward In Vivo Applications

Abstract: Molecularly imprinted polymers (MIPs), synthetic polymeric receptors, have been combined successfully with thermal transducers for the detection of small molecules in recent years. However, up until now they have been combined with planar electrodes which limits their use for in vivo applications. In this work, a new biosensor platform is developed by roll-coating MIP particles onto thermocouples, functionalized with polylactic acid (PLLA). As a first proof-of-principle, MIPs for the neurotransmitter dopamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 38 publications
0
37
0
Order By: Relevance
“…In previous work, 27 the authors described polylactic acid (PLLA) coated thermocouples that were impregnated with MIP particles. The PLLA-sheet (∼2 μm thickness) forms a thermally insulating layer around the thermocouple over the entire sheet within the flow cell.…”
Section: Thermal Measurements Of Nanomips Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous work, 27 the authors described polylactic acid (PLLA) coated thermocouples that were impregnated with MIP particles. The PLLA-sheet (∼2 μm thickness) forms a thermally insulating layer around the thermocouple over the entire sheet within the flow cell.…”
Section: Thermal Measurements Of Nanomips Sensorsmentioning
confidence: 99%
“…With the dose-response curve and obtained fit, a LoD value of 3 ± 1 nM in PBS was estimated, which was an improvement of nearly three orders of magnitude compared to previous works on thermocouples. 27 The explanation behind this is threefold; first, there is a ten-fold decrease in layer thickness that promotes heat-flow through the surface and increases the response to changes in the thermal signal and, second, the increased surface-to-volume ratio of the nanoparticles and, third, the higher affinity of the nanoMIPs towards its template. It is also an improvement compared to the more conventional approach where MIP particles were functionalised onto an electrode surface rather than directly on the thermocouple, which attained LoDs between 25-100 nM for small molecules in buffered solutions.…”
Section: Thermal Experiments With Thermocouples Functionalized With Nmentioning
confidence: 99%
See 1 more Smart Citation
“…MIP particles for small molecules are often made in an external reaction vessel and need to be deposited onto the planar measurement electrode using an immobilization layer made by, e.g., spin coating or dip coating. In the latter case, it was recently demonstrated that it is possible to dip coat thermocouples with DNA and roll coat them with polymeric particles for the direct detection of molecules in aqueous media without the need of planar electrodes . Although, this approach is promising, the smaller contact area of the thermocouple limits the sensitivity of the methodology.…”
Section: Introductionmentioning
confidence: 99%
“…When template molecules bind to the MIP receptor layer, the thermal resistance increases and detection of serotonin in buffer solutions in the low nanomolar regime was demonstrated [ 21 ]. The thermal readout platform could be combined with various other receptors leading to other biosensing applications, such as DNA mutation analysis, phase changes in lipids, and detection of cells, but biological samples remained to be evaluated [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%